Circulatory microRNAs in helminthiases: Potent as diagnostics biomarker, its potential role and limitations - Ullah, Hanif; Tian, Yali; Arbab, Safia; Li, Ka; Khan, Muhammad Inayat Ullah; Rahman, Sajid Ur; Qadeer, Abdul; Muhammad, Nehaz; Suleman,; Hassan, Inam Ul (Frontiers in Veterinary Science, 2022)
Infections caused by helminths are responsible for severe public health problems and economic burden on continental scale. Well-timed and precise diagnosis of helminth infections is critical for taking by appropriate approaches for pathogen control. Circulating miRNAs are stable diagnostic tool for different diseases found in a variety of body fluid. As diagnostic biomarkers in infectious diseases, miRNAs detection in body fluids of helminth infected hosts is growing promptly. Uncovering miRNAs is a relatively new tool, used for early-stage detection of helminth infection from experimental or non-invasive clinical samples. miRNAs can be detected in body fluids such as serum, saliva, urine, and tissues of helminth infected host, mainly blood offering important benefits for diagnosis accurately. In this review, we discuss different characteristics of helminth parasite-derived circulating and EV miRNAs, supporting its potential uses in for helminth diagnosis and treatment efficiency.